The Quality Services of University Education from the students’ point of view -A field study at Faculty of Education in Tishreen University - - Mobayed, Mouhannad Mohamad (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The research aims to identify the Availability the quality services of university education at Faculty of Education in Tishreen University from the students’ point of view, also to define the differences in the degree of the research sample about the Availability the quality services of university education at Faculty of Education in Tishreen University according to these variables (sex, study year). The present research used the descriptive analytical approach, and to achieve the objectives of the research, questionnaire has been consisted of (40) statements distributed into four sections for the quality services of University, were applied on sample (132) students at Faculty of Education in Tishreen University during the academic year of (2018 – 2019). Validity of the questionnaire was established though a jury of (7) of the teaching staff of educational at Tishreen University. Pilot sample consisted of (38) students at Faculty of Education in Tishreen University Reliability was established through Cronbach – Alpha Reliability (0.937). The research results showed that the Availability the quality services of university education at Faculty of Education in Tishreen University were middle rated from the view point of the the students’. In fact there are no found differences between the answers of sample research about the Availability the quality services of university education at Faculty of Education in Tishreen University according to the variable (sex), but there are found differences in the degree it’s found according to the variable (study year), in favor of four and five years. The research provided some suggestions such as interest of the University with the quality of the services which provide its, and participate the students in improvement of the university services.